Impact de Marteilia refringens et de Bonamia ostreae sur l'ostréiculture bretonne - Grizel, Henri (Actes CIEM, CM 1983/Gen : 9, 1983)
Two successive diseases struck the flat oyster Ostrea edulis farms in Brittany. These two epizooties lead to some changes in the farming practices. The oyster culture developed towards the open ocean, in the sublitoral part. New techniques have been developed for the culture and collection. The flat oyster has been partially replaced by the cupped oyster Crassostrea gigas whose production went from 3 000 to 16 000 tonnes. They also had heavy consequences on the regional economy. The important mortalities decimated the stocks. The production dropped by about 17 000 tonnes from 1910 to 1982. For the same period of time, profits from the sale of the produced flat oysters dropped from 131.6 million to 65.2 million francs. Numerous companies reduced the surface of their offshore exploitations and the manpower employment decreased progressively. A rescue plan was set up, with the help of the State, in order to try and stop the development of the disease and restart flat oyster production. Deux maladies successives ont frappé les élevages d'huîtres plates, Ostrea edulis, en Bretagne. Ces deux épizooties ont entrainé des modifications dans les pratiques culturales. L'ostréiculture s'est développée vers le large, dans la partie sublittorale. De nouvelles techniques ont été mises au point pour l'élevage et le captage. L'huître plate a été en partie remplacée par l'huître creuse Crassostrea gigas dont la production est passée de 3000 à 16 000 tonnes. Elles ont eu également de graves conséquences sur l'économie régionale. Les mortalités importantes ont décimé les stocks. La production a baissé d'environ 17 000 tonnes de 1910 à 1982. Pour la même période le chiffre d'affaire de la vente d'huîtres plates à la production est passé de 131,6 millions à 65,2 millions de francs. De nombreuses entreprises ont réduit en mer leur surfa.ce d'exploitation et l'emploi de main d'oeuvre a régulièrement regressé. Un plan de sauvegarde a été mis en place, avec l'aide de l'état pour essayer d'enrayer le développement de la maladie et ...